Does Socializing in the Virtual World Impact Victimization in the Real World?. Issue 3 (February 2023) - Boccio, Cashen M.; Leal, Wanda E.
Previous research links unstructured socializing with victimization. In addition, recent research also links digital media use with particular forms of online victimization (e.g., cyberbullying, harassment, sex solicitation, phishing, computer viruses, etc.). Very limited research, however, has explored how socialization through virtual means (e.g., using social networking sites, video chatting, and texting) is associated with in-person victimization. This is a pertinent gap in the literature as trends in adolescent socializing have been shifting from spending time in-person to spending more time socializing through virtual means. As a result, the current state of the literature cannot adequately assess the risks that may be posed by spending time engaging in virtual socializing. This article addresses this gap in the literature by examining the relationship between virtual socializing and several indicators of in-person victimization (i.e., property, violent, and in-school bullying victimization) along with one indicator of online victimization (i.e., cyberbullying) in a nationally representative sample of adolescents. Specifically, our study utilizes negative binomial regression and logistic regression to test associations between time spent using social networking sites, video chatting, texting, and phone usage and in-person victimization using data drawn the 2018 eighth and tenth grade cohort of Monitoring the Future . Our findings reveal that time spent engaging in virtual socializing activities is associated with a greater likelihood of property, violent, in-school bullying, and online bullying victimization. In addition, these associations remain significant when taking into account time spent engaging in in-person unstructured socializing. The implications of these findings for future research and policy are discussed.